Analysis of the effects of mineral admixtures on the strength of mortars: Application of the predictive model of Feret - Boudchicha, Abdelaziz; Zouaoui, Mustapha Cheikh; Gallias, Jean-Louis; Mezghiche, Bouzidi (Journal of Civil Engineering and Management, 2007)
The introduction of fine and ultra‐fine mineral admixtures in cementing materials generates a granular effect, a physico‐chemical and micro‐structural effect and, possibly, chemical effect. To analyse the specific share of each effect, we propose to use a methodology based on a volume substitution of cement by admixtures in mixes whose absolute volume of the solid phases and workability are preserved constant and then only the effects of the particles of admixtures in the cementing phase are taken into account. We expressed the compressive strength of mortars with admixtures according to a factor of compactness by applying to the mortars the principles of the predictive model of Feret. This factor makes possible to distinguish the modifications generated by the granular effect of the admixtures on the compactness of the cementing matrix independently of the physico‐chemical and chemical effects. The specific chemical action of each admixture has been evaluated by analysing the variation of the coefficient of activity K according to the rate of the cement substitution, by applying to the studied mortars the concept of the equivalent binder and by deducing the coefficient of activity from the predictive model of Feret.Mineralinių priedų įtakos skiedinių stipriui analizė Feret modelio taikymasSantrauka. Smulkių ir labai smulkių mineralinių priedų naudojimas cementiniuose skiediniuose sukelia fizikinius, cheminius bei mikrostruktūrinius efektus. Šiems efektams įvertinti siūloma metodika, pagal kurią cemento kiekis skiedinio mišinyje pakeičiamas mineralinių priedų kiekiu taip, kad mišinio slankumas lieka nepakitęs. Skiedinių su priedais stipris gniuždant, atsižvelgiant į sutankinimo laipsnį, nustatytas, taikant Feret modelį. Tai leidžia išskirti priedų įtaką cementinio akmens sutankjimui nepriklausomai nuo fizikinių ir cheminių procesų. Kiekvieno priedo cheminis poveikis buvo įvertintas analizuojant aktyvumo koeficiento K kitimą pagal pakeičiamo cemento kiekį. Analiz taip pat atlikta taikant ekvivalentinio rišiklio koncepciją bei aktyvumo koeficientą, nustatytą taikant Feret modelį.Reikšminiai žodžiai: skiedinys, mineraliniai priedai, vandens poreikis, tankumas, stipris, fizinis ir cheminis efektas, Feret modelis.First Published Online: 14 Oct 2010